40 Forms of Selenium in Vitamin-Mineral Mixes Differentially Affect the Expression of Genes Responsible for Prolactin and ACTH Synthesis in Pituitaries of Steers Grazing Endophyte-Infected Tall Fescue. (1st March 2018) - Li, Q; Jia, Y; Bridges, P; Matthews, J C
Abstract: Summer-long grazing of mixed forages containing endophyte-infected tall fescue (E+) inhibits expression of genes (PRL, prolactin; DRD2, dopamine receptor D2; POU1F1, POU class 1 homeobox 1; POMC, proopiomelanocortin; PCSK1, proprotein convertase subtilisin/kexin type 1) encoding proteins responsible for prolactin and POMC/ACTH synthesis by the pituitaries of growing beef steers consuming vitamin-mineral mixes containing 35 ppm inorganic Se (sodium selenite, ISe). The objective of the current study was to test the hypothesis that forms of Se (ISe, organic (OSe, SEL-PLEX), or a 1:1 blend (MIX) of ISe and OSe) in vitamin-mineral mixes will differentially affect the mRNA content of the above genes in the pituitaries of beef steers grazing E+. Predominately-Angus steers (BW= 183 ± 34 kg) were randomly selected (n = 8) from herds of fall-calving cows grazing E+ pasture and consuming vitamin-mineral mixes that contained 35 ppm Se as ISe, OSe, or MIX forms. Calves were weaned, depleted of Se for 90 d, and assigned to summer-long grazing of a common E+ pasture (0.51 ppm total ergovaline/ergovalinine; 10.1 ha). Selenium treatments were administered by top-dressing 85 g of a common basal vitamin-mineral mixes that contained 3 mg Se/d (35 ppm Se) onto 0.23 kg soyhulls, using in-pasture Calan gates. All steers consumed all offered mineral mix every day. The effect of Se treatment on serum prolactin concentrations at day 0, 22, 43, 64, and 86 was analyzed using the PROC MIX procedure of SAS. After slaughter at day 93 through 119, total RNA was isolated from whole pituitaries, RT-PCR analysis of target genes was conducted, and the relative content of mRNA for proteins associated with prolactin and ACTH synthesis was compared by ANOVA using the GLM procedure of SAS. Fisher's protected LSD procedure was used to separate all treatment means. Serum prolactin decreased over time (P < 0.01) for all Se treatment groups but was greater (P < 0.05, MIX > OSe > ISe) for MIX and OSe steers. The mRNA content of PRL (OSe > ISe, OSe > MIX), DRD2 (OSe > ISe), POU1F1 (MIX > ISe), and POMC (OSe > ISe, OSe > MIX) differed (P < 0.05) among Se treatments, whereas mRNA content of GAL, VIP, and PCSK1 was not affected. We conclude that the form of Se as MIX vs OSe in vitamin-mineral mixes differentially affects the expression of genes responsible for prolactin and ACTH synthesis in the pituitaries of growing beef steers consuming E+ pasture.